Rough surface contact under creep conditions. (December 2022) - Alamos, Fernando J.; Philo, Martin; Go, David B.; Schmid, Steven R.
Abstract: A pressing concern in superplastic forming (SPF) is the ability to quantitatively model to effectively design tooling and assess process viability. Current finite element method simulations for SPF generally do not include the evolutionary nature of friction under creep conditions. The presence of creep strain leads to junction growth and saturated contact areas at longer time scales than conventional metal forming; therefore, friction models that ignore creep-induced strains will underpredict asperity contact and friction levels. In this work, a new micro-contact model of a rough surface in contact with a rigid flat surface is created to predict asperity flattening under creep behavior. A semi-empirical equation of the real contact area and friction at different SPF conditions is established. Highlights: A predictive friction model for superplastic forming is established. A predictive contact model for rough surfaces under creep is develop. Normal loading and straining of the bulk conditions are considered. The contact area growth follows a general exponential decay function. A characteristic time described analytically from the constitute model is derived.